2021
DOI: 10.3390/rs13040673
|View full text |Cite
|
Sign up to set email alerts
|

Studies of FY-3 Observations over the Past 10 Years: A Review

Abstract: With the rapid advances and abundant observations from Chinese Fengyun-3 (FY-3) meteorological satellites, it is of great interest to summarize a decade of quality assessments of FY-3 observations. The topics covered are noise characterization, bias estimation, striping noise detection and mitigation of striping noise, radio frequency interference detection, geolocation accuracy estimation and improvement, data assimilation cloud detection and quality control for observations from the MicroWave Temperature Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…FY-3D, as the fourth satellite, was launched on 15 November 2017. It is jointly networked with FY-3C to improve the accuracy of atmospheric detection and enhance the capabilities of greenhouse gas monitoring, comprehensive space environment detection, and meteorological remote sensing detection [38,39]. The FY-3D L1 level data used in this article can be downloaded from the National Satellite Meteorological Center (http://satellite.nsmc.org.cn/portalsite/default.aspx (accessed on 27 May 2022)).…”
Section: Data Sourcesmentioning
confidence: 99%
“…FY-3D, as the fourth satellite, was launched on 15 November 2017. It is jointly networked with FY-3C to improve the accuracy of atmospheric detection and enhance the capabilities of greenhouse gas monitoring, comprehensive space environment detection, and meteorological remote sensing detection [38,39]. The FY-3D L1 level data used in this article can be downloaded from the National Satellite Meteorological Center (http://satellite.nsmc.org.cn/portalsite/default.aspx (accessed on 27 May 2022)).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Microwave imagers are an important category of space‐based instruments that measure upwelling microwave radiation from the surface and atmosphere. Examples of microwave imagers placed on board satellites include the Advanced Microwave Scanning Radiometer 2 (AMSR2) on board the Global Change Observation Mission Water Cycle ( GCOM‐W ) satellite (JAXA, 2013), the Special Sensor Microwave Imager Sounder (SSMIS) on board the Defense Meteorological Satellite Program ( DMSP ) satellites Kunkee et al (2008), the MicroWave Radiation Imager (MWRI) on board the Fengyun‐3D ( FY‐3D ) satellite Zou (2021), and the Global Precipitation Measurement (GPM) Microwave Imager (GMI) Hou et al (2014). Recent studies have shown that microwave imager observations have great potential to improve atmospheric analyses and forecasts for both regional and global NWP Kazumori et al (2016); Yang et al (2016); Geer et al (2010); Pu et al (2019); Lean et al (2017); Geer and Bauer (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate forecasting of typhoon track and intensity is of great significance in reducing the enormous losses they cause in terms of assets, human casualties, and economic impacts [3]. In recent years, the utilization of radiance data from microwave sounders has emerged as a crucial aspect in studies concerning numerical weather prediction (NWP) and its correlation with climate [4,5]. Several microwave sounders have been developed and employed for atmospheric observations.…”
Section: Introductionmentioning
confidence: 99%